2012
DOI: 10.1002/hipo.22032
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile, but not adult exposure to high‐fat diet impairs relational memory and hippocampal neurogenesis in mice

Abstract: Increased consumption of high-fat diet (HFD) leads to obesity and adverse neurocognitive outcomes. Childhood and adolescence are important periods of brain maturation shaping cognitive function. These periods could consequently be particularly sensitive to the detrimental effects of HFD intake. In mice, juvenile and adulthood consumption of HFD induce similar morphometric and metabolic changes. However, only juvenile exposure to HFD abolishes relational memory flexibility, assessed after initial radial-maze co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
194
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(214 citation statements)
references
References 37 publications
19
194
1
Order By: Relevance
“…Our results indicate that hippocampal newly-born neurons were decreased in the high fat diet-fed mice compared to the control diet-fed mice, which is consistent with the previous findings reported by several studies (Boitard et al, 2012;Gault et al, 2015;Hamilton et al, 2011;Hwang et al, 2008;Klein et al, 2016;Park et al, 2010;Pathak et al, 2015;Rivera et al, 2013;Vinuesa et al, 2016;Yoo et al, 2011aYoo et al, , 2011bYoo et al, , c, d, 2012Yoo et al, , 2014. In addition, our results indicate that psychological stress using a Communication Box caused a significant decrease in the DCX-positive neuroblasts/immature neurons in the hippocampus of the high fat diet-, but not in the control diet-fed mice.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our results indicate that hippocampal newly-born neurons were decreased in the high fat diet-fed mice compared to the control diet-fed mice, which is consistent with the previous findings reported by several studies (Boitard et al, 2012;Gault et al, 2015;Hamilton et al, 2011;Hwang et al, 2008;Klein et al, 2016;Park et al, 2010;Pathak et al, 2015;Rivera et al, 2013;Vinuesa et al, 2016;Yoo et al, 2011aYoo et al, , 2011bYoo et al, , c, d, 2012Yoo et al, , 2014. In addition, our results indicate that psychological stress using a Communication Box caused a significant decrease in the DCX-positive neuroblasts/immature neurons in the hippocampus of the high fat diet-, but not in the control diet-fed mice.…”
Section: Discussionsupporting
confidence: 95%
“…We previously found that hippocampal neurogenesis is increased by chronic administration of tandospirone, a clinically available 5-HT1A receptor partial agonist with anxiolytic and antidepressant effects, under stress and non-stress conditions (Mori et al, 2014;Murata et al, 2015). Many researchers have reported that neurogenesis in the hippocampal DG is decreased in rodents with a chronic intake of obesogenic diets, including a high fat diet (Boitard et al, 2012;Gault et al, 2015;Hamilton et al, 2011;Hwang et al, 2008;Klein et al, 2016;Park et al, 2010;Pathak et al, 2015;Rivera et al, 2013;Vinuesa et al, 2016;Yoo et al, 2011aYoo et al, , b, c, d, 2012Yoo et al, , 2014. Of interest, recent data demonstrate that a decrease in hippocampal neurogenesis contributes to the dysregulation of the hypothalamuspituitary-adrenal (HPA) axis and the activation of a stress response (Dranovsky and Leonardo, 2012;Snyder et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Although there are some controversial results, it seems that a high fat diet leads to a decrease in proliferation of NSPCs (Lindqvist et al, 2006;Park et al, 2010;Boitard et al, 2012), whereas caloric restriction has beneficial effects on neurogenesis, probably due to increased survival of newborn neurons (Lee et al, 2000;2002). However the mechanisms are poorly understood and whether NSPCs and their progeny are directly altering their metabolic program upon major changes incirculating nutrients is not known.…”
Section: Environmental Impact On Adult Neural Stem Cell Metabolismmentioning
confidence: 95%
“…For instance, hippocampal and amygdala functioning are similarly affected by the amount of time individuals have been exposed to a Western diet. More specifically, it has been shown that a Western diet impacts hippocampal [12]) and amygdala functioning [13] more in the juvenile period than in the adult period. They found similar results for amygdalian functioning.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…However, while this consumption impairs hippocampal-dependent memory, it may increase the amygdala-dependent one [131]. Moreover, the impact of a Western diet is faster on hippocampal functioning than on amygdala functioning, as the hippocampal functioning changes earlier than the amygdalian one [12,13]. It is however not currently known to what extent the hippocampal functioning's change may drive the amygdalian one.…”
Section: Outstanding Questionsmentioning
confidence: 99%